Smart Marketing Round in Promoting Marketing Recovery ‎A Case Study of a Tire Manufacturing Company in A Najaf ‎Al Ashraf Governorate - Almayali, Mohmmed T. Kahnger; Azeez, Ihsan AbdUlAmeer; Bahr, Afaf Hussein Mohammed; Yasir, Mohammed Hameed (International Journal of Accounting and Economics Studies, 2026)
This research seeks to explain the dimensions of intelligent marketing represented by (attraction, communication, sharing, retention ‎, and learning) as an independent variable in the research of marketing recovery as the dependent variable, within the framework of ‎the general tire industry in Al-Najaf Governorate. The research started from a discussion problem formulated in a group of ‎intellectual and field questions, the most important being the extent of ownership of the researched company to the dimensions of the ‎research variables, in addition to revealing the nature of the correlation and influence relationships between these variables. We try to ‎answer these questions by exploring the theoretical and practical implications of the variables under study, as they are among the ‎modern topics in the working environment of the company where the study is conducted. To achieve the objectives of the research, ‎the questionnaire was designed to collect data, and it was placed on a sample of the company’s employees, with the distribution of 49 ‎questionnaires, out of which 43) valid questionnaires for statistical analysis. The response rate reached 88%. The researchers relied ‎on descriptive and analytical statistical methods in data analysis using SPSS V.24 software, and the research reached a group of ‎conclusions and proposals. I highlight the conclusions of the existence of a spiritual relationship between the dimensions of smart ‎marketing and marketing recovery in the research sample, and it also shows that the dimensions of smart marketing have a spiritual ‎effect on marketing recovery at the overall level. In the light of these results the theme of presenting a group of suggestions, the most ‎important of which is the need for the company under study to adopt effective and sustainable policies to keep up with ‎environmental changes, to contribute to strengthening the image of marketing recovery in the minds of customers and ‎supporting the powers of competition and staying in the market for a long time.